2010
DOI: 10.1111/j.1464-410x.2009.09014.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Blockers to assist stone clearance after extracorporeal shock wave lithotripsy: a meta‐analysis

Abstract: Study Type – Therapy (meta‐analysis)
Level of Evidence 1a OBJECTIVE To review the evidence for the use of α‐blockers after extracorporeal shock wave lithotripsy (ESWL) in enhancing the effectiveness of renal and ureteric stone clearance. METHODS We searched MEDLINE, Embase and the Cochrane Library up to January 2009. All randomized controlled trials in which α‐blockers were evaluated after ESWL were eligible for the analysis. Outcome measures assessed were clearance rate (primary) and expulsion time (secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 33 publications
2
50
1
1
Order By: Relevance
“…The authors identified seven trials that met the inclusion criteria and found that the use of alpha-blockers, which was tamsulosin in all seven studies, improved SWL success by 16%. 47,[51][52][53][54][55][56][57] The authors also reported reduced time to fragment passage, reduced pain, and required less analgesia.…”
Section: Alpha Blockersmentioning
confidence: 99%
“…The authors identified seven trials that met the inclusion criteria and found that the use of alpha-blockers, which was tamsulosin in all seven studies, improved SWL success by 16%. 47,[51][52][53][54][55][56][57] The authors also reported reduced time to fragment passage, reduced pain, and required less analgesia.…”
Section: Alpha Blockersmentioning
confidence: 99%
“…22 Various studies and practical's done for checking the efficacy of tamsulosin it was observed that mean expulsion time of tamsulosin was about 15 days. 23 Choi et al, conducted a study that alpha blocker post lithotripsy showed excellent results than calcium channel blocker post ithotripsy. 24 Kim et al 25 documented results between alpha blocker and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Zhu Y, et al in a meta analysis concluded that treatment with tamsulosin after ESWL appears to be effective in assisting stone clearance in patients with renal and ureteral calculi. 11 All these above mentioned studies have used tamsulosin alone as an adjunctive procedure to ESWL and have found it to be effecticve. In our experience addition of deflazacort, a low dose steroid, will significantly improve the ESWL outcomes.…”
Section: Discussionmentioning
confidence: 99%